Asthma in Pregnancy: Pathophysiology, Diagnosis, Whole-Course Management, and Medication Safety - Huijie Wang; Na Li; Huaqiong Huang (Canadian Respiratory Journal)
Asthma in pregnancy is a health issue of great concern. Physiological changes and drug compliance during pregnancy can affect asthma control in varying degrees, and the control level of asthma and the side effects of asthma medications are closely related to the adverse perinatal outcomes of mother and fetus. This article provides an update on the available literature regarding the alleviating or aggravating mechanism of asthma in pregnancy, diagnosis, disease assessment, and systematic management, to provide a new guidance for physician, obstetric joint doctor, and health care practitioner.